THE IMPLEMENTATION MAKE A MATCH MODELS IN TIK SUBJECT TO IMPROVE THE LEARNING RESULTS AND STUDENS’ LEARNING ACTIVENESS OF CLASS VII E ACADEMIC YEAR 2011/2012 IN SMP NEGERI 2 KUBUTAMBAHAN - Wahyu Sugiarsa, Komang (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2012)
This research was aimed at (1) improving the students’ learning results in TIK subject of class VII E SMP Negeri 2 Kubutambahan through the implementation of make a match models (2) improving the students’ learning activeness in TIK subject of class VII E SMP Negeri 2 Kubutambahan through the implementation of make a match models  (3) investigating the students’ response of class VII E SMP Negeri 2 Kubutambahan toward the implementation of make a match models in TIK subject.The design of the research was a Classroom Action Research which consisted of two cycles.  Each cycle consisted of four steps namely planning, action, observation and evaluation, and reflection. The subject of this research was the students of class VII E SMP Negeri 2 Kubutambahan in academic year 2011/2012. The class consisted of 35 students.  Meanwhile, the objects of this research were (1) students’ learning results (2) students’ learning activeness (3) students’ response toward the implementation of    make a match models in TIK subject. The data of students’ learning results in TIK subject were collected through the test and observation, data of students’ learning activeness in TIK subject were collected trough the observation, and the data of students’ response were collected through questionnaire. The collected data was analyzed by using descriptive analysis.Based on the analysis of data obtained, this research showed that the students’ learning results got improvement. Cycle I, the mean of students’ scores was 67 and the percentage of students’ classical success was 71%, as for cycle 2, the mean of students’ scores was 80 and the percentage of students’ classical success was 91%. The students’ learning activeness got improvement, in cycle I the mean of students’ scores was 50 and for cycle 2, the mean of students’ scores was 61. The students’ responses toward the implementation of make a match models in TIK subject come in positive category with a mean of 84%.